Charcot-Marie-Tooth disease type 4J with spastic quadriplegia, epilepsy and global developmental delay: a tale of three siblings. (3rd August 2022) - Chaudhuri, Jasodhara; Dutta, Atanu Kumar; Biswas, Tamoghna; Biswas, Atanu; Ray, Biman Kanti; Ganguly, Gautam
Abstract: Charcot-Marie-Tooth (CMT) disease is mainly a disease of peripheral nervous system and patients typically present with features of demyelinating neuropathy or axonal neuropathy or both. Rarely patients present with features of central nervous system involvement. Parkinsonism, aphemia and familial epilepsy syndrome have previously come up as case reports in association with CMT type 4 J.We hereby describe a family with 3 siblings affected with CMT4J with homozygous FIG4 mutation who presented with global developmental delay, epilepsy and spastic quadriparesis.